Continuous improvement in the Netherlands: current practices and experiences in Dutch manufacturing industry. (1st January 1997) - Gieskes, Jose F.B.; Baudet, Frank; Schuring, Roel W.; Boer, Harry
In order to get insight into the current continuous-improvement practices in European industry, EuroCINet carried out a survey in its member countries. In this article, continuous-improvement activities in a sample of 135 Dutch industrial companies are described. The results show that CI is a relatively new development for companies in the Netherlands and the main motivators to start CI are costs, delivery reliability and quality. Many companies are starting a process of CI; few, however, have a sustained process. CI is widespread through companies and not limited to the manufacturing departments. However, less than 50 per cent of all employees are actively engaged in CI activities. The survey revealed that for companies it is difficult to measure the effect of CI and link these results to market requirements.